Hatékonyság a nyelvhelyességi kérdések oktatásában - Csernicskó István; Черничко Степан; Csernicsko Istvan; Márku Anita; Марку Аніта (Újvidéki Egyetem Bölcsészettudományi Karának Magyar Tanszéke, 2001)
Írásunkban egy a magyar nyelvművelő irodalomban kiemelten tárgyalt nyelvhelyességi kérdés, az -e kérdőszócska szórendi helye kapcsán mutatjuk be, hogy a kárpátaljai magyar oktatás jelenlegi hatékonyságát a standard norma elsajátíttatása terén.

Abstract. Hungarian language education has been making efforts for long decades to inform, „acquaint” the general public with problems of correct usage. School education is also highly concerned with teaching good usage. By means of questionnaires based on a representative sample we we were seeking an answer to how effective this has proved in practice among the Hungarian secondary school leavers in the Sub-Carpathia region. In our research we touched upon the most accentuated problems of correct usage. We dealt with what is called „suksüköles, szukszüköles, nakozäs”, certain instances of hypercorrection, certain dialectical peculiarities, the effects of bilingualism, and also with some lexical variables. Our choice of informants is representative of the last grade of secondary school students, therefore the results that we have obtained shed light upon how effective the teaching of Hungarian language is with regard to correct usage or to be more precise, on how well-informed the school-leavers are about the way their school treats certain usage variants that are usually stigmatised by Hungarian language cultivation.
Effectivness in Teaching Correct Usage
http://real.mtak.hu/25144/1/2001_Hatekonysag_a_nyelvhelyessegi_kerdesek_oktatasaban_u.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/126618
Keywords: oktatás; nyelvhelyességi kérdések; kárpátaljai magyar oktatás